Don’t blame women for low libido. Sexual sparks fly when partners do their share of chores – including calling the plumber - Buzwell, Simone; Johansen, Eva (The Conversation, 2022)
When a comic about “mental load” went viral in 2017, it sparked conversations about the invisible workload women carry. Even when women are in paid employment, they remember their mother-in-law’s birthday, know what’s in the pantry and organise the plumber. This mental load often goes unnoticed. Women also continue to do more housework and childcare than their male partners. This burden has been exacerbated over the recent pandemic (homeschooling anyone?), leaving women feeling exhausted, anxious and resentful. As sexuality researchers, we wondered, with all this extra work, do women have any energy left for sex?
Keywords: 2000 à aujourd'hui; 2020-2029; australie; charge mentale; discipline; désir; océanie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexologie; sexualité; thématiques

Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

Coronavirus, domestic labour and care: Gendered roles locked down - Craig, Lyn (Journal of Sociology, 2020)
The Covid-19 pandemic turned daily lives upside down. Lockdowns and physical distancing meant hundreds of thousands of people switched to working from home, significantly blurring the temporal and spatial boundaries between paid work, domestic labour and caring for others. This article explores gender relations, and the division of employment, domestic labour and care, drawing on early results from an online survey, Work and Care in the Time of Covid-19, carried out between 7 May and 4 June 2020.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; australie; care; covid-19; discipline; division sexuelle du travail; océanie; pandémie; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sociologie; soins aux enfants; thématiques; travail; travail de reproduction; travail invisible